Candida albicans cell wall mannosidases, Dfg5 and Dcw1, regulate chitin synthesis. Issue 12 (17th December 2021) - Maddi, Abhiram; Kim, Jaewon; Sohi, Harleen; Busarajan, Sujay; Glagovyak, Olga; Knapp, Madlin; Chinnici, Jennifer
Abstract : In Candida albicans chitin synthesis is important for cell wall integrity and may also have a role in emergence of drug-resistance. Our past studies showed that cell wall mannosidases, Dfg5 and Dcw1, regulate HOG MAPK signaling. In this study, we investigated how Dfg5 and Dcw1 regulate chitin synthesis by affecting HOG, PKC and Calcium-Calcineurin signaling pathways. DFG5 and DCW1 heterologous mutants (ES1 & ES195) and a conditional mutant (ES195+methionine/cysteine) were utilized. WT SC5314 served as negative control and Hog1 knock-out mutant as positive control. Fluorescence microscopy of calcofluor white (CFW) stained mutant and control strains was performed to observe chitin accumulation. Quantitative PCR analysis was performed to measure the relative expression of chitin synthases CHS1, CHS2, CHS3 and CHS8. Incubation with chitinase was done to determine cell separation using light microscopy and scanning electron microscopy (SEM) analysis. Fluorescence microscopy showed significantly increased chitin accumulation in the mutants as compared to wild type. Chitin accumulation was observed mainly at the budding sites indicating a cause for defective cell separation phenotype. Incubation with chitinase led to cell separation in the mutants. CHS2, CHS3 and CHS8 expression was observed to be significantly upregulated in the conditional mutant and HOG1 mutant as compared to the wild type. This upregulation was also observed when the cell wall integrity PKC pathway was activated. However, activation of the Calcium-calcineurin pathway downregulated chitin synthase expression in the mutants. Our data indicates that Dfg5 and Dcw1 regulate expression of chitin synthases via HOG MAPK, PKC and Calcium-calcineurin signaling pathways.